Transgenic Bt Cotton Does Not Disrupt the Top-Down Forces Regulating the Cotton Aphid in Central China. - Yong-Sheng Yao; Peng Han; Chang-Ying Niu; Yong-Cheng Dong; Xi-Wu Gao; Jin-Jie Cui; Nicolas Desneux (PLoS ONE, 2016)
Top-down force is referred to arthropod pest management delivered by the organisms from higher trophic levels. In the context of prevalent adoption of transgenic Bt crops that produce insecticidal Cry proteins derived from Bacillus thuringiensis (Bt), it still remains elusive whether the top-down forces are affected by the insect-resistant traits that introduced into the Bt crops. We explored how Bt cotton affect the strength of top-down forces via arthropod natural enemies in regulating a non-target pest species, the cotton aphid Aphis gossypii Glover, using a comparative approach (i.e. Bt cotton vs. conventional cotton) under field conditions. To determine top-down forces, we manipulated predation/parasitism exposure of the aphid to their natural enemies using exclusion cages. We found that the aphid population growth was strongly suppressed by the dominant natural enemies including Coccinellids, spiders and Aphidiines parasitoids. Coccinellids, spiders and the assemblage of other arthropod natural enemies (mainly lacewings and Hemipteran bugs) are similarly abundant in both plots, but with the parasitoid mummies less abundant in Bt cotton plots compared to the conventional cotton plots. However, the lower abundance of parasitoids in Bt cotton plots alone did not translate into differential top-down control on A. gossypii populations compared to conventional ones. Overall, the top-down forces were equally strong in both plots. We conclude that transgenic Bt cotton does not disrupt the top-down forces regulating the cotton aphid in central China.